2014
DOI: 10.1016/j.jvs.2013.04.044
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Gore Hybrid Vascular Graft in a challenging high-lying extracranial carotid artery aneurysm

Abstract: Extracranial carotid artery aneurysm is a rare condition with relatively significant morbidity and mortality. When surgery is not indicated, endovascular techniques are emerging as the preferred treatment. However, even this approach may be contraindicated due to anatomic factors. We present a case of a high-lying extracranial carotid artery aneurysm with challenging anatomy unsuitable for conventional or endovascular repair. After resecting the aneurysm, the carotid artery was revascularized using the new Gor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…In addition, covered stent was not an option for a kinked ICA with an aneurysm because of the difficulty of endovascular approach and high embolization risk. Nigro et al [25] suggested a hybrid technique with a more favorable outcome, which consisted of surgical shortening of the proximal ICA to adjust the kinking followed by stent placement. This technique was also used in 1 case of our series.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, covered stent was not an option for a kinked ICA with an aneurysm because of the difficulty of endovascular approach and high embolization risk. Nigro et al [25] suggested a hybrid technique with a more favorable outcome, which consisted of surgical shortening of the proximal ICA to adjust the kinking followed by stent placement. This technique was also used in 1 case of our series.…”
Section: Discussionmentioning
confidence: 99%
“…Possibly, the lack of a suitable conical stent could have been dealt with by releasing multiple covered stents with gradually increasing calibers overlapping each other, using tapered stent-grafts. [11][12][13][14][15][16] However, the long-term efficacy of this endovascular option is lacking evidence from studies, especially in the topography of the knee joint. Furthermore, endovascular surgery is not available at the service where this patient was treated.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] The first large experience with the use of GHVG was recently reported by Chiesa et al 29 to address RAs during open TAAA repair. Their experience with 25 patients reported satisfactory results that are at least comparable to those of standard renal revascularization.…”
Section: Discussionmentioning
confidence: 99%